Effect Of Levels And Sources Of Protein On The Performance And Nutrient Digestibility In Black Bengal Goat - Ullah, MB; Islam, KMS; Akbar, MA; Khaleduzzaman, ABM; Debi, MR (Bangladesh Journal of Animal Science, 2012)
Sixteen castrated male Black Bengal goats (aged between 8 and 10 months and average live weight 9.16 kg) were used in a 2 × 2 factorial design to study the effect of protein levels and sources on growth and nutrient digestibility under intensive condition for 56 days. The sources of protein were mustard oil cake (MOC) and soybean meal (SBM). Level of protein in each sources were 22 (HP-high protein) and 16 (LP-low protein) percentage. The dietary treatments were (T1) MOC-HP, (T2) MOC-LP, (T3) SBM-HP and (T4) SBM-LP. Concentrate diets as well as dal grass was fed throughout the experimental period and last week considered for digestibility trial. Average daily live weight gain of goats was 42, 41, 43, and 52 g for the diets T1, T2, T3 and T4 respectively. The result showed no significant (P>0.05) variation between protein sources and their levels on growth performance. Intake of DM was 425, 389, 407 and 437 g/d which were 4.2, 3.8, 4.0 and 4.1 percent of their body weight for the diets T1, T2, T3 and T4 respectively. Intake of CP was 59, 46, 56 and 50 g/d respectively. The sources of protein did not influence the intake of CP (P>0.05), but their levels had (P<0.05) effect on it. Digestibility of DM was 62, 58, 69 and 68 percent respectively. OM digestibility (g/100g) was 67, 64, 71 and 73 for the diets T1, T2, T3 and T4 respectively. Digestibility (g/100g) of CP was 62, 60, 70 and 69 for the diets T1, T2, T3 and T4 respectively. Thus the result showed that the digestibility of DM, CP and OM was significantly higher for SBM than MOC but their levels varied insignificantly. Therefore low protein supplementation (16%) in a concentrate mixture containing mustard oil cake and/or soybean meal could be suggested for optimizing growth performance of Black Bengal Goat under intensive management system. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9912 BJAS 2009; 38(1-2): 53-60